Quarter-life Crisis ditinjau dari Intoleransi Ketidakpastian pada Emerging Adult dengan Coping Religius sebagai Moderator - Rifqa Amalia Azzyati; Nida Ul Hasanat (UIN Sunan Kalijaga, 2025)
Quarter-life crisis refers to a psychological crisis characterized by confusion in identity exploration, feelings of helplessness, and anxiety related to future uncertainty experienced during emerging adulthood. Religious coping is viewed as one of the strategies used to manage psychological crises. This study explored the moderator effect of religious coping between intolerance of uncertainty and quarter-life crisis among emerging adults in Indonesia. Using a quantitative approach, data were collected through a survey involving 301 participants, employing the Quarter-Life Crisis Scale, the Indonesian version of IUS-12, and the Indonesian version of Brief RCOPE. Based on Moderated Regression Analysis (MRA), religious coping did not function as a moderator between intolerance of uncertainty and quarter-life crisis. Multiple regression analysis revealed that religious coping and intolerance of uncertainty jointly served as variables that significantly predicted of quarter-life crisis. Quarter-life crisis merujuk pada krisis psikologis yang ditandai dengan kebingungan dalam eksplorasi identitas, perasaan tidak berdaya, dan kecemasan mengenai ketidakpastian masa depan yang cenderung dialami pada fase emerging adulthood. Sementara itu, coping religius dipandang sebagai salah satu upaya untuk mengatasi krisis psikologis. Penelitian ini mengeksplorasi peran coping religius sebagai moderator antara intoleransi ketidakpastian serta quarter-life crisis pada emerging adult di Indonesia. Dengan pendekatan kuantitatif, data dikumpulkan melalui survei terhadap 301 partisipan menggunakan Skala Quarter-life Crisis, IUS-12 versi Indonesia, dan Brief RCOPE versi Indonesia. Berdasarkan Moderated Regression Analysis (MRA), coping religius tidak berperan sebagai moderator antara intoleransi ketidakpastian dan quarter-life crisis. Dari analisis regresi ganda, coping religius dan intoleransi ketidakpastian bersama-sama berperan signifikan sebagai prediktor quarter-life crisis.